The Rise of AI in Everyday Life: How Artificial Intelligence Affects Students (Journal of Universal Science Research, 2023)
In the contemporary educational landscape, Artificial Intelligence (AI) is reshaping students' experiences through personalized learning, enhanced critical thinking, creative exploration, and career preparation. This article delves into the transformative effects of AI on education, highlighting its potential benefits while addressing privacy concerns and the need for a balanced human-AI interaction. From tailor-made learning paths to fostering creativity and easing career choices, AI is steering education towards a future of innovation and adaptability.